Bedside quantitative electroencephalography improves assessment of consciousness in comatose subarachnoid hemorrhage patients. Issue 4 (16th August 2016) - Claassen, Jan; Velazquez, Angela; Meyers, Emma; Witsch, Jens; Falo, M. Cristina; Park, Soojin; Agarwal, Sachin; Michael Schmidt, J.; Schiff, Nicholas D.; Sitt, Jacobo D.; Naccache, Lionel; Sander Connolly, E.; et al.
Abstract : Objective: Accurate behavioral assessments of consciousness carry tremendous significance in guiding management, but are extremely challenging in acutely brain‐injured patients. We evaluated whether electroencephalography (EEG) and multimodality monitoring parameters may facilitate assessment of consciousness in patients with subarachnoid hemorrhage. Methods: A retrospective analysis was performed of 83 consecutively treated adults with subarachnoid hemorrhage. All patients were initially comatose and had invasive brain monitoring placed. Behavioral assessments were performed during daily interruption of sedation and categorized into 3 groups based on their best examination as (1) comatose, (2) arousable (eye opening or attending toward a stimulus), and (3) aware (command following). EEG features included spectral power and complexity measures. Comparisons were made using bootstrapping methods and partial least squares regression. Results: We identified 389 artifact‐free EEG clips following behavioral assessments. Increasing central gamma, posterior alpha, and diffuse theta‐delta oscillations differentiated patients who were arousable from those in coma. Command following was characterized by a further increase in central gamma and posterior alpha, as well as an increase in alpha permutation entropy. These EEG features together with basic neurological examinations (eg, pupillary light reflex) contributed heavily to a linear model predicting behavioral state, whereas brain physiology measures (eg, brain oxygenation), structural injury, and clinical course added less. Interpretation: EEG measures of behavioral states provide distinctive signatures that complement behavioral assessments of patients with subarachnoid hemorrhage shortly after the injury. Our data support the hypothesis that impaired connectivity of cortex with both central thalamus and basal forebrain underlies decreasing levels of consciousness. Ann Neurol 2016;80:541–553